2012
DOI: 10.3146/ps10-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Virginia Market Type Genotype on Peanut Response to Weed Interference

Abstract: Differences in the ability of cultivars to compete with weeds are not well-defined for peanut. Research was conducted in 2007 and 2008 to compare the growth and competitiveness of the virginia market type cultivars NC 10C, NC-V 11, NC 12C, Phillips, VA 98R, and breeding lines N99027L, N01013T, and N02020J under weedy and weed-free conditions. Weed-free peanut was established by applying preemergence and postemergence herbicides throughout the growing season supplemented by weekly hand removal of weeds. Clethod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 22 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…The results indicated that despite their differences in growth habit and canopy architecture, the four evaluated cultivars responded similarly to weed interference (Table 1). Place et al (2012) compared biomass production of eight Virginia market type peanut genotypes growing under weed-free and weedy conditions, but all genotypes responded similarly to weed interference. They concluded that, at least for Virginia market type peanut, efforts to select cultivars with higher weed suppression and competition tolerance might have little value as part of an integrated weed management approach due to the limited genetic variability for these traits.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results indicated that despite their differences in growth habit and canopy architecture, the four evaluated cultivars responded similarly to weed interference (Table 1). Place et al (2012) compared biomass production of eight Virginia market type peanut genotypes growing under weed-free and weedy conditions, but all genotypes responded similarly to weed interference. They concluded that, at least for Virginia market type peanut, efforts to select cultivars with higher weed suppression and competition tolerance might have little value as part of an integrated weed management approach due to the limited genetic variability for these traits.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, efforts to increase competitive tolerance to weeds should emphasize experimental approaches that allow characterization of peanut sensitivity to weed interference. However, it might be necessary to evaluate peanut types other than those studied in the present research and by Place et al (2012) to increase the likelihood of finding genetic material with higher potential for weed suppression and interference tolerance…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations